ANTI-TERROR POLICY OF UZBEKISTAN IN THE FRAMEWORK OF THE REGIONAL ANTI-TERRORIST POLICY OF THE SCO - Bazyleva, S.P. (RUDN Journal of Political Science, 2017)
The beginning of the XXI century was marked by a number of serious problems, including cancer, world hunger, environmental problems and increasing every year the problem of global terrorism, which poses a great threat to the security of the modern multipolar world. Uzbekistan today occupies a firm position in fight against terrorist threat. The principled position of Uzbekistan in the fight against terrorism is that “no country should exclude their participation in the fight against global terrorism, there must be no transit zones and "green corridors" for terrorist organizations”. The Central Asian region is one of the most vulnerable, because it is necessary to pay special attention to the strategy of the anti-terrorist security of the countries included in the structure of the Central Asian region. In this article, we consider the anti-terrorist policy of Uzbekistan in the framework of the regional anti-terrorist policy of the SCO.